Service quality in the healthcare sector: the role of strategic human resources planning - Adedoyin, Samuel A.; Fakorede, Elizabeth; Oyakhire, Victor A. (Management and Entrepreneurship: Trends of Development, 2026)
The study evaluated the influence of strategic human resources planning on service quality in selected healthcare organizations in Benin City, Nigeria. Specifically, it examined how succession planning, focused learning and development, and workforce audits influenced service quality in the healthcare sector. The study utilized a cross-sectional research design executed through a survey involving a sample of 275 respondents. This sample was derived from 860 employees being the total population of the three participating healthcare organizations purposively selected for the study. The research instrument was a well structured instrument designed in the Likert scale format. The validity of the instrument was assured through face and content validation techniques, while the reliability was assured through the Cronbach alpha statistic test, which yielded alpha values greater than 0.70 acceptable reliability value threshold for empirical studies. Three hypotheses in alignment with the study objectives were raised and tested using simple linear regression analysis, and at 5% level of significance. The findings revealed that succession planning, focused learning and development and workforce audits all had significant influence on service quality improvements in the sampled health organizations. The study concluded that the strategic human resource planning components examined positively influenced service quality in the healthcare organizations. It was recommended among other things that healthcare organizations should ensure continued policies and initiatives that support succession planning and uphold systematic, well-structured, focused learning and development programmes for employees to improve their service quality.JEL Classification: M10, M11, M30.